2022
DOI: 10.5114/jcb.2022.113547
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative interstitial high-dose-rate brachytherapy for keloids scar

Abstract: Purpose: To evaluate the results of keloids treated with perioperative interstitial high-dose-rate brachytherapy (HDR-BT).Material and methods: A retrospective review of 61 keloids in 51 patients treated with perioperative interstitial HDR-BT was performed. Keloid lesions were treated with 12 Gy in 4 fractions within 48 hours. Time between surgery and brachytherapy was less than 90 minutes. Local failure was defined as recurrence of apparent keloid or symptoms in the same place. Median age of patients was 46 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Keloids in other locations were more irregular in shape, had high tension, and had a relatively low local control rate, which was similar to the results of previous studies. [19][20][21][22][23][24] As in the general population, hypertension was more common among older patients in this study. Although univariate analysis suggested that hypertension was a prognostic factor for the need for postoperative adjuvant electron RT for keloids, multivariable analysis revealed that it was not an independent factor.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Keloids in other locations were more irregular in shape, had high tension, and had a relatively low local control rate, which was similar to the results of previous studies. [19][20][21][22][23][24] As in the general population, hypertension was more common among older patients in this study. Although univariate analysis suggested that hypertension was a prognostic factor for the need for postoperative adjuvant electron RT for keloids, multivariable analysis revealed that it was not an independent factor.…”
Section: Discussionsupporting
confidence: 51%
“…Keloids in other locations were more irregular in shape, had high tension, and had a relatively low local control rate, which was similar to the results of previous studies. [19–24]…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Barragán et al published their findings on 51 patients with 61 lesions who received HDR-IRT, reporting a recurrence rate of 4.9% when using 12 Gy in four fractions, with all recurrences being in the thorax. They suggested that increasing the dose at this location could be beneficial [ 20 ]. Liao et al successfully treated seven complex keloids in three patients with HDR-IRT using 6 Gy × 3 fractions and observed no recurrences at a 9-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of treatment effect, the control of RT treatment dose and irradiation time is particularly important. The total recommended dose for treating keloids ranges from 12 to 20Gy, with the maximum biologically effective dose is 30Gy, but the degree of damage to visceral organs remains to be determined (50,51). In addition to treatment modality, anatomical location is a key factor affecting the recurrence rate, the highest in the chest and lowest in the ear (49).…”
Section: Radiation Therapymentioning
confidence: 99%